Cocaina on the road: On the global origin of the drug problem from the Opium issue in Asia. - Scheerer, Sebastian (2022)
The transformation of the 19th century’s “opium question” into the 20th century’s “drug problem” is normally seen as a mere response to growing availability of and demand for psychoactive drugs. This hegemonic view is being challenged by an alternative perspective that stresses the contingencies in the constitution of the social problem and reveals how, at different crossroads, things could have taken quite a different turn. Using the emergence of the international prohibition regime over cocaine (1909-1919) it is shown how the politically motivated inclusion of cocaine in The Hague Convention of 1912 paved the way for an otherwise highly improbable “world law” against numerous psychoactive drugs as well as for the emergence of the very category of “drug problem” which otherwise possibly never would have come into existence.